38.7k views
5 votes
How do you solve "z+ma=ba" solve for a

User Sisi
by
6.6k points

2 Answers

1 vote
Hi there,

Z = Ma = ba

You made a typo. One of those = signs should either
be a + and a -. Here are all possibilities:


1. Z+Ma = ba, solve for a
Ma-Ba = -Z
a(M-B) = -Z
a = -Z/(M-B)

2. Z = Ma+ba, solve for a
Ma+ba = Z
a(M+b) = Z
a = Z/(M+b)

3. Z-Ma = ba, solve for a
Z = Ma+ba
Ma+ba = Z
a(M+b) = Z
a = Z/(M+b)

4. Z = Ma-ba, solve for a
Ma-ba = Z
a(M-b) = Z
a = Z/(M-b)

Hope it helps.
User Idle Sign
by
6.8k points
5 votes
z+ma=ba
ma-ba=-z
a(m-b)=-z

a=(-z)/(m-b)
User Amna Arshad
by
6.3k points